FACTORIAL ANALYSIS RELATED TO FAMILY PREPAREDNESS FACING DISASTER IMPACT IN TERNATE CITY OF MALUKU UTARA PROVINCE - Syafrudin Lukman Ahmad; Ahsan Ahsan; Mukhamad Fathoni (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Disasters occur when vulnerable people are faced with threats that they are unable to cope with or have low capacity to overcome them. Preparedness is the most critical phase in the range of disaster management, the inadequacy of disaster preparedness planning has created the suffering of survivors and loss of life. The purpose of this study was to analyze factors related to family preparedness in Ternate city. This research use descriptive analytic design with Cross sectional study approach. Respondents in this study were 113 Head of Family (KK) by using systematic random sampling. Chi-square test shows the related relationship (p = 0,005), attitude (p = 0.000) and social capital (p = 0.000) to risky family preparedness in Ternate city. The result of logistic regression test shows that social capital has the strongest strength of relationship (p = 0,022, OR = 2,725) compared to attitude (p = 0,025, OR = 2,680) and knowledge (p = 0,041, OR = 2,520). His result shows that good knowledge, attitude and social capital will increase the family preparedness in the face of disaster impact in Ternate City.